The Skirts of the Great City - D'Anvers, N., 1844-1933; Bell, Arthur George, 1849-1916 (Salt Lake City, UT : Project Gutenberg, 2015)
"The Skirts of the Great City" by Mrs. Arthur G. Bell is a historical account focusing on the suburban areas adjacent to London, written in the early 20th century. The work delves into the rich histories, notable landmarks, and cultural significance of various neighborhoods and villages surrounding the great metropolis. Particularly, it begins by discussing Hampstead and its captivating past, providing insights into how these areas evolved over time against a backdrop of significant historical events. The opening of the volume explores Hampstead's history, emphasizing its transformation from a humble village into a fashionable suburb due to its natural springs and health resorts. It introduces various elements such as the ancient manor, associations with historical figures, and the overall atmosphere that influenced its development. The narrative also reflects on the impact of the larger city of London as it enveloped these outlying communities, urging readers to recognize the intertwined stories that give character to each suburb. Highlights include discussions of local governance, architectural changes, and social dynamics that shaped the identity of Hampstead and its surroundings through the years. (This is an automatically generated summary.)
Release date is 2015-06-29
Produced by Al Haines
Keywords: Suburbs -- England -- London